Environmental pollution and emission factors of electronic cigarettes, heat-not-burn tobacco products, and conventional cigarettes. Issue 6 (3rd June 2017) - Ruprecht, A. A.; De Marco, C.; Saffari, A.; Pozzi, P.; Mazza, R.; Veronese, C.; Angellotti, G.; Munarini, E.; Ogliari, A. C.; Westerdahl, D.; Hasheminassab, S.; Shafer, M. M.; et al.
ABSTRACT: The increasing popularity of electronic cigarettes (e-cigarettes) and, more recently, the new "heat-not-burn" tobacco products (iQOS) as alternatives to traditional tobacco cigarettes has necessitated further documentation of and research into the composition and potential health risks/benefits of these devices. In a recent study, we compared second-hand exposure to particulate metals and organic compounds from e-cigarettes and traditional cigarettes, by conducting continuous and time-integrated measurements in an indoor environment, followed by computing the emission rates of these species using a single-compartment mass balance model. In this study, we have used a similar approach to further expand our previous analyses by characterizing black carbon, metal particles, organic compounds, and size-segregated particle mass and number concentrations emitted from these devices in addition to the newly marketed iQOS. Analysis of the iQOS side-stream smoke indicated that the particulate emission of organic matter from these devices is significantly different depending on the organic compound. While polycyclic aromatic hydrocarbons (PAHs) were mostly non-detectable in the iQOS smoke, certain n-alkanes, organic acids (such as suberic acid, azelaic acid, and n-alkanoic acids with carbon numbers between 10 and 19) as well as levoglucosan were still emitted in substantial levels from iQOS (up to 2–6 mg/h during a regular smoking regimen). Metal emissions were reduced in iQOS smoke compared to both electronic cigarettes and conventional cigarettes and were mostly similar to the background levels. Another important finding is the presence of carcinogenic aldehyde compounds, including formaldehyde, acetaldehyde, and acrolein, in iQOS smoke, although the levels were substantially lower compared to conventional cigarettes. Copyright © 2017 American Association for Aerosol Research